Ḥadīts Sebagai Ḥujjah Ḥukum dalam Perspektif Syī‘ah - Ahmad Ali (Refleksi: Jurnal Kajian Agama dan Filsafat, 2012)
This article shows that in the Shī‘ite (Shī‘a) madhhab (school) is different opinion concerning Ḥadīth/Sunna as ḥujja (allegation of law). One faction states that all aspects of the Prophet’s life are ḥujja, whilst another party claims that only some aspects of his life i.e. the aspect which connotes tashrī‘(law guidance) can be a ḥujja. In between these two sides, the most appropriate view point is the latter one, for it is more objective and proportional in looking at him as an ordinary human being, in one dimension, and as an apostle, in another one. The controversy then has enlarged into the ḥujja of ḥadīth/khabar al-āḥād. For some people, khabar al-āḥād is absolutely refused; another some admits it absolutely; while some receives it under certain prerequisites; and even a number of scholars accept it with the very tight and stiff requisites. In this context, again, the least group’s idea is more objective, logic and contextual. This conclusion is resulted from uṣūl al-fiqh approach and philosophical analysis.DOI: 10.15408/ref.v13i3.907